Discriminant analysis of fast food consumption behavior among university students: a case study - Nurita, Fonna; Umam, Khairul; Yuni, Cut; Tanjung, Azbar; Ansari, Marzuki (Jurnal Geuthèë: Penelitian Multidisiplin, 2025)
A shift in dietary patterns towards fast-food consumption, including among university students, has the potential to impact health and lifestyle. This study aimed to analyze the factors that differentiate fast-food consumption behavior (frequent versus infrequent categories) among students of the Mathematics Education Study Program, academic year 2022-2024, at Syiah Kuala University in Banda Aceh. Using a quantitative descriptive approach with a survey method, data were collected through questionnaires from 59 respondents. Fisher's discriminant analysis was employed to classify consumption behavior. The findings reveal that the majority of students (35 out of 59) fell into the frequent consumption category, indicating a need for closer attention to the dietary patterns of this group. Based on the analysis of discriminant function coefficients, the most influential factors in differentiating consumption behavior were lifestyle, service quality, a varied menu, an affordable price, and a strategic location. The discriminant model demonstrated an accuracy of 81.4% on cross-validated cases, indicating an effective predictive capability. The implications of this research highlight an urgent need for nutritional education interventions and policies that support healthy eating patterns to curb the fast-food consumption trend among students and the wider community, considering the significant health risks associated with this behavior.